2011
DOI: 10.1016/j.ejcts.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Von Willebrand syndrome is an early-onset problem in ventricular assist device patients

Abstract: The AVWS is present already in the early postoperative phase after VAD implantation. Therefore, reduced shear stress has to be an important feature of newly developed assist devices in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 23 publications
4
69
1
2
Order By: Relevance
“…AvWS is among the most discussed factor, and it results from mechanical destruction and proteolysis of the HMWM of vWF, induced by shear stress. 10-12 In accordance with Heilmann et al, 10 our entire HMII population showed loss of the HMWM of vWF, indicating AvWS; however, not all patients showed bleeding. The 13 patients with the most number of recurrent bleeding events, which necessitated AT cessation, had significantly lower vWF:CBA/vWF:Ag ratio than the rest of our HMII patients.…”
Section: Discussionsupporting
confidence: 67%
“…AvWS is among the most discussed factor, and it results from mechanical destruction and proteolysis of the HMWM of vWF, induced by shear stress. 10-12 In accordance with Heilmann et al, 10 our entire HMII population showed loss of the HMWM of vWF, indicating AvWS; however, not all patients showed bleeding. The 13 patients with the most number of recurrent bleeding events, which necessitated AT cessation, had significantly lower vWF:CBA/vWF:Ag ratio than the rest of our HMII patients.…”
Section: Discussionsupporting
confidence: 67%
“…[4][5][6][7][8][9] It has been demonstrated that acquired VWF deficiency can be detected within days after implantation of an axial continuous flow left ventricular assist device (LVAD). 10 We and others 11,12 also demonstrated that the VWF deficiency present in patients with AS is corrected within days after its surgical treatment. Based on in vitro studies, it was inferred that unfolding and cleavage of the VWF A2 domain in vivo could occur within 200 seconds in response to acute changes in shear conditions.…”
Section: Circulation Researchmentioning
confidence: 99%
“…Although it has been demonstrated that the loss of HMW multimers could be observed the day after the initiation of LVAD support, 10 the initial response of VWF multimers after induction of high shear in vivo was unknown. The dynamic onset of shear-induced proteolysis of HMW multimers has been extensively described in vitro.…”
Section: Dynamic Variations In Hmw Multimers In Response To Acute Chamentioning
confidence: 99%
“…Die Ergebnisse stimmen größtenteils mit früheren Studien überein, welche darauf hinweisen, dass das AVWS schon sehr früh nach Implantation eines LVAD vorliegt und nach LVAD-Explantation reversibel ist (Heilmann et al, 2011;Uriel et al, 2010). …”
Section: Erworbenes Von Willebrand-syndrom (Avws)unclassified